Vasculitis mimics. Part 2. Large and medium vessel vasculitis mimickers: genetic vasculopathies. Mimickers of small vessel vasculitis - G. M. Tarasova; O. N. Egorova; T. M. Reshetnyak; B. G. Issayeva; D. S. Dilmanova; N. M. Maripkhan (Современная ревматология)
Genetic vasculopathies can mimic large and medium vessel vasculitis, while occlusive non-vasculitic vasculopathies and infections are often mimickers of small and medium vessel vasculitis. Most of these conditions are as severe as systemic vasculitides but require fundamentally different, and often urgent treatment approaches.